Natural logarithm-based sliding mode control for two DOF active engine mounting system - Wijaya, Andika Aji; Darsivan, Fadly Jashi; Wahyudi, Martono; Akmeliawati, Rini (2009)
The needs of powerful engine and lighter car body has adverse effect to the vibration occurred in the car. Obviously the presence of the engine vibration will imposed to the discomfort of the driver and passengers as well. To isolate the vibration, active engine mounting (AEM) has been proposed as the new generation of engine mounting. The control method becomes key factor of successfulness of AEM system. This paper presents a control method using natural logarithm-based sliding mode control (ln-SMC) for two degree-of-freedom (DOF) active engine mounting system. The performance of the controller is evaluated by applying sinusoidal and random disturbance to the system. Robustness of the proposed controller can be evaluated by increasing magnitude of the disturbance. The result shows that proposed control method not only able to attenuate the vibration of the different types of disturbance but also robust for magnitude variation of disturbance.